The importance of corporate culture in enhancing the governance of joint-stock companies - Akramova, Nazokat (Goodwood Publishing, 2025)
Purpose: This study examines the role of corporate culture in strengthening the governance mechanisms of joint-stock companies. This study aims to conceptualize how cultural values interact with governance structures to shape accountability and ethical conduct. Research methodology: A qualitative descriptive approach was applied by synthesizing philosophical, normative, and organizational frameworks from literature published between 2000 and 2023. Content analysis identified recurring themes such as values, rituals, and leadership patterns, with Deal and Kennedy’s four-level model used to assess the cultural influence on governance. Results: In Uzbekistan’s current economic renewal, joint-stock companies such as “Uzsalaman” JSC and “Maxam Chirchiq” JSC seek to improve efficiency through market alignment, equipment modernization, and cultural development. Evaluating efficiency requires sector-based indicators of cost, profit, and output, as well as internal and external conditions. A multi-indicator system offers a more accurate performance measurement that is consistent with international standards. Conclusions: Effective governance requires cohesive, value-driven teams that reinforce formal structures and shared goals. Strategic cultural programs should focus on motivation, communication, and management, aligning with organizational conditions. A strong corporate culture enhances productivity, reduces turnover, and supports governance outcomes. Limitations: This study is conceptual and does not include field-based data from joint stock companies. Contribution: This study provides a theoretical foundation linking culture with governance effectiveness and offers strategic insights for enhancing organizational performance in joint-stock enterprises.